Record power profile in elite Olympic cross-country mountain bike cyclists: Normative values and fatigue effects - Sánchez-Jiménez, J. L.; Javaloyes, A.; Peña-González, I.; Moya-Ramón, M.; Mateo-March, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This study aimed to establish normative maximum mean power (MMP) values for elite cross-country mountain bike (XCO) cyclists across various durations (5 s to 5 min) under fresh and fatigued conditions, analyze differences in MMP between these states, and compare performance between Top 10 and Top 11-140 cyclists. A retrospective observational study analyzed power output data from 693 elite male XCO race files (2020-2024). Cyclists were categorized into Top 10 (n = 72) and Top 11-140 (n = 621) groups. MMP was measured in absolute (W) and relative (W kg-1) terms under fresh (early race) and fatigued (last lap) conditions, with cumulative energy expenditure (kJ) as a control variable. Data were cleaned for anomalies, non-parametric tests were used to assess differences, and correlations explored relationships between race result, energy expenditure, and MMP. Absolute MMP was higher under fresh conditions (first lap, mean energy expenditure: 188 ± 35 kJ) across all durations, with significant decreases in fatigued states (last lap, cumulative energy expenditure: 1250 ± 210 kJ; p < 0.001, effect size = 1.0). Top 10 cyclists outperformed the Top 11-140 group (p < 0.001, effect sizes = 0.3-0.6), showing greater energy expenditure (p < 0.001). Similar patterns were observed in relative terms, with some exceptions for very short efforts. Performance consistency was evident, with strong correlations between durations and conditions. Elite XCO cyclists exhibit distinct MMP profiles, with notable declines due to fatigue, particularly in short efforts. Top 10 cyclists demonstrate superior performance and workload capacity, highlighting the need for balanced anaerobic and aerobic training to excel in XCO racing, especially in the final lap.